PROFIT AND SALARY - MOTIVATING FACTORS AT THE ORGANIZATIONAL LEVEL - ALINA NIȚESCU (Annals of the University of Petrosani: Economics, 2021)
The market economy presupposes the development of economic activities that are characterized, first of all, by efficiency, this realizing the connection between the allocated resources and the obtained results. An activity is the more efficient when a higher value of production is obtained with the same amount of production factors used, or when a given amount of results is obtained with a minimum consumption of production factors. Thus, an economic activity is characterized by efficiency when profit is made - which is the main goal and also the motivating factor of any entrepreneur. In order to increase the efficiency of the labour production factor, an important role is played by the reward system, where the salary has a primordial place.